Performing weight change : a performative reading of reality-making through a relationship of meaning and doing : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in English at Massey University - Caseley, Allyson June (Massey University, 2009)
Reading the reality-making processes that create bodies in weight change performances challenges us to understand the relationships between meanings and actions, or between discourses and materiality. This study uses a performative model to elaborate how discourses and materiality can be read in texts in such a way to bring transparency to the process of materiality-making, agency and causality. The texts used in this study are transcribed interviews of participants who identified themselves as undergoing weight change. Reading weight and body-making as a discursive-material relationship enriches a shared understanding in the interdisciplinary space of psychology and English. The performative model chosen for this study offers sufficient structure to read both the generic features of reality-making and individually-nuanced reality-making practices, presenting psychologists with a sophisticated understanding of change processes. To read reality-making with detailed transparency, we require tools of analysis that can directly read discourses and actions as shared spaces of relationship, through which material entities can emerge. For such tools of analysis, this study utilizes and extends the model of performativity offered by Dr Karen Barad (2007). In using this model to read text performatively, the unique features that are creating performances of weight change are accessed through a reading of boundary-making practices, through the relationship between meaning and doing that establishes what matters in accessing possibilities for meaning and possibilities for doing, and through the elaboration of subject-object relationships into a sequenced performance.
Keywords: Weight gain; Weight loss; Obesity; Psychological aspects; Body image; Performative (Philosophy); Discourse analysis